Peer norms moderate the association between mental health and sexual risk behaviors among young men living in Dar es Salaam, Tanzania. (January 2018) - Hill, L.M.; Moody, J.; Gottfredson, N.C.; Kajula, L.J.; Pence, B.W.; Go, V.F.; Maman, S.
Abstract: Background: Young men living in Dar es Salaam's informal settlements face environmental stressors that may expose them to multiple determinants of HIV risk including poor mental health and risky sexual behavior norms. We aimed to understand how these co-occurring risk factors not only independently affect men's condom use and sexual partner concurrency, but also how they interact to shape these risk behaviors. Methods: Participants in the study were male members of 59 social groups known as "camps" in Dar es Salaam, Tanzania. We assessed moderation by changes in peer norms of the association between changes in symptoms of anxiety and depression and sexual risk behaviors (condom use and sexual partner concurrency) among 1113 sexually active men. Participants nominated their three closest friends in their camp and reported their perceptions of these friends' behaviors, attitudes, and encouragement of condom use and concurrency. Anxiety and depression were measured using the HSCL-25, and condom use and sexual partner concurrency were assessed through self-report. Results: Perceptions of decreasing condom use among friends (descriptive norms) and decreasing encouragement of condom use were associated with lower levels of condom use. Perceptions of increasing partner concurrency and acceptability of partner concurrency (injunctive norms) among friends were associated with higher odds of concurrency. Changes in perceived condom use norms (descriptive norms and encouragement) interacted with changes in anxiety symptoms in association with condom use such that the negative relationship was amplified by norms less favorable for condom use, and attenuated by more favorable norms for condom use. Conclusions: These results provide novel evidence of the interacting effects of poor mental health and risky sexual behavior norms among a hard to reach population of marginalized young men in Dar es Salaam. Our findings provide important information for future norms-based and mental health promotion interventions targeting HIV prevention in this key population. Highlights: Assessed interaction of co-occurring risk factors: mental health and peer norms. Men's perceptions of peer norms do not match peers' reported behaviors. Changes in perceived descriptive norms and peer encouragement linked to condom use. Increased anxiety coupled with riskier peer norms meant less condom use. Changes in perceived norms was associated with partner concurrency.